Do law professionals lack economic knowledge? - Hassid, Joseph; Maniatis, George; Polemis, Michael (Economics and Business Letters, 2026)
This study examines the relevance of economic knowledge among lawyers, based on a survey of Greek law professionals. The econometric results unveil a gap between the perceived usefulness and adequacy of economics literacy by lawyers. We argue that graduate studies in economics increase perceived competence, while self-employed practice is less beneficial. The findings survive robustness checks when we account for demographic characteristics. Lastly, the empirical analysis underscores the value of continued education and the impact of professional business experience in deepening lawyers' understanding of economics.